2022
DOI: 10.14202/vetworld.2022.1456-1466
|View full text |Cite
|
Sign up to set email alerts
|

Implications of sperm heat shock protein 70-2 in bull fertility

Abstract: Heat shock protein 70 (HSP70) is one of the most abundant chaperone proteins. Their function is well documented in facilitating the protein synthesis, translocation, de novo folding, and ordering of multiprotein complexes. HSP70 in bovine consists of four genes: HSP70-1, HSP70-2, HSP70-3, and HSP70-4. HSP70-2 was found to be involved in fertility. Current knowledge implicates HSP70-2 in sperm quality, sperm capacitation, sperm–egg recognition, and fertilization essential for bull reproduction. HSP70-2 is also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 101 publications
1
7
0
Order By: Relevance
“…Chen et al [26] have previously reported that the mRNA for HSP70 is involved in biological functions, especially in energy metabolism processes for sperm motility. Our study has also demonstrated a strong correlation between HSP70-2 and motility (p<0.01) (Table 5), thus reinforcing the hypothesis put forth by Chen et al [26] that, part addition to being involved in energy metabolism processes, HSP70 also prevents apoptosis due to heat stress and modulates the balance between dead and living cells [7]. Ramesha et al [27] also reported that HSP70, which plays a role in spermoocyte recognition, is found on the surface of the sperm plasma membrane, in the acrosome region, and is also detected during the capacitation process.…”
Section: Discussionsupporting
confidence: 90%
“…Chen et al [26] have previously reported that the mRNA for HSP70 is involved in biological functions, especially in energy metabolism processes for sperm motility. Our study has also demonstrated a strong correlation between HSP70-2 and motility (p<0.01) (Table 5), thus reinforcing the hypothesis put forth by Chen et al [26] that, part addition to being involved in energy metabolism processes, HSP70 also prevents apoptosis due to heat stress and modulates the balance between dead and living cells [7]. Ramesha et al [27] also reported that HSP70, which plays a role in spermoocyte recognition, is found on the surface of the sperm plasma membrane, in the acrosome region, and is also detected during the capacitation process.…”
Section: Discussionsupporting
confidence: 90%
“…Heat stress damages developing spermatozoa. However, heat tolerance can be inherited by offspring ( 3 ). According to the relevant literature, Madura cattle are a native breed of beef cow thought to have developed on the dry and barren island of Madura ( 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, heat tolerance can be inherited by offspring ( 3 ). According to the relevant literature, Madura cattle are a native breed of beef cow thought to have developed on the dry and barren island of Madura ( 3 ). Madura Island receives 1600 mm of rain annually and is hot and arid ( 31 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations